Institutional quality, FDI inflows, human capital development and poverty: a case of Indonesia - Goh, Lim Thye; Trinugroho, Irwan; Law, Siong Hook; Rusdi, Dedi (Emerald Publishing, 2024)
PurposeThe objective of this paper is to investigate the impact of institutional quality, foreign direct investment (FDI) inflows and human capital development on Indonesia’s poverty rate.Design/methodology/approachThe quantile regression on data ranging from 1984 to 2019 was used to capture the relationship between the impact of the independent variables (FDI inflows, institutional quality and human capital development) on Indonesia’s poverty rate at different quantiles of the conditional distribution.FindingsThe empirical results reveal that low-quantile institutional quality is detrimental to poverty eradication, whereas FDI inflows and human capital development are significant at higher quantiles of distribution. This implies that higher-value FDI and advanced human capital development are critical to lifting Indonesians out of poverty.Practical implicationsPolicymakers should prioritise strategies that advance human capital development, create an enticing investment climate that attracts high-value investments and improve institutional quality levels.Originality/valueThis study contributes to the existing literature because, compared to previous studies that focussed on estimating the conditional mean of the explanatory variable on the poverty rate. It rather provides a more comprehensive understanding of the quantiles of interest of FDI inflows and institutional quality on the Indonesian poverty rate, allowing for more targeted policies.